Soybean protein in milk replacer diets for baby pigs - G L Allee; P Hsu; R S Prather (Kansas Agricultural Experiment Station Research Reports, 1981)
Two trials, involving 108 pigs, were conducted to evaluate the effects of replacing milk protein with various levels of soybean protein in milk replacer diets. Pigs fed diets in which 25 or 50% of the milk protein was replaced with a modified soybean had weight gains and efficiencies similar to those of pigs fed the all-milk-protein diet, but incidence of scours decreased. Protein digestibility decreased as the level of soybean protein in the diet increased. These results suggest that 25 to 50% of the milk protein in a 28% protein milk replacer diet can be replaced with a modified soybean protein, thereby greatly reducing feed cost.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Soybean protein; Milking replacer; Digestibility